The mysterious Benedict Society and the prisoner's dilemma - Stewart, Trenton Lee (Stewart, Trenton Lee. Mysterious Benedict Society series., 2009)
When an unexplained blackout engulfs Stonetown, Benedict Society members Reynie, Kate, Sticky, and Constance follow clues on an adventure that threatens to separate them from their families, friends, and even one another.